Fiqh Al Ta’wil Wa Al Tafsir: Hermeunetika Pandangan Abdullah Saeed Dalam Karya“Intrepreting The Qur’an: Towards A Contemporary Approach” - Raikhan Raikhan (ALAMTARA: Jurnal Komunikasi dan Penyiaran Islam, 2018)
This paper attempts to elaborate the thought of Abdullah Saeed, a man Islamic thinkers who have a concentration on the interpretation of the Qur'an. As a scholar who studied Middle Eastern education and education in the Western world (Saeed), Saeed tries to offer a new approach in understanding the text of the Qur'an according to the social historical context at the time of the acceptance of the 7th century CE and adjusted to the conditions and needs of Muslims today. In the discourse of Islamic thought, the Koran has a significant position. This is not Islam as scriptural faith has necessitated the Islamic society to pay serious attention to the revealed text, especially in answering the problems of modernity. The Qur'an is a book of religious and moral principles and advice for mankind.